Projective Technique Reveals Unconscious Attitudes about Poverty in Canada. Issue 6 (2nd November 2018) - Mitchell, Terry; Loomis, Colleen; Polillo, Alexia; Fry, Brooke; Mackeigan, Mary
ABSTRACT: Canada has been challenged in attempts to reduce and eliminate poverty. In this study, the authors used a projective technique to assess attitudes about people living in poverty (113 young adults, average age 21) living in southwestern Ontario. Five themes emerged from Thematic Apperception Test responses: (1) negative assumptions about people in poverty, (2) simplified beliefs about various pathways into poverty, (3) conditional compassion for those living in poverty, (4) gendered responses about women in poverty, and (5) individualized attitudes and beliefs about pathways out of poverty. Findings have implications for shifting victim-blaming explanations for why people are living in poverty.